2012
DOI: 10.1503/cmaj.120427
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and causes of end-stage renal disease among Aboriginal children and young adults

Abstract: Background: Although Aboriginal adults have a higher risk of end-stage renal disease than non-Aboriginal adults, the incidence and causes of end-stage renal disease among Aboriginal children and young adults are not well described. Methods:We calculated age-and sex-specific incidences of end-stage renal disease among Aboriginal people less than 22 years of age using data from a national organ failure registry. Incidence rate ratios were used to compare rates between Aboriginal and white Canadians. To contrast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 25 publications
(30 reference statements)
3
9
0
Order By: Relevance
“…While El Salvador study by, Orantes et al reported family history of CKD was positive in 21.6% of the study population [17]. In this series GN as a cause of CKD reported in 18% of patients, while Samuel reported GN Aboriginal children and young adults have increased risk of ESRD mostly due to GN in people ≤ 40 years of age [18]. Samuel et al report agrees with the incidence reported with our results.…”
Section: Discussionsupporting
confidence: 88%
“…While El Salvador study by, Orantes et al reported family history of CKD was positive in 21.6% of the study population [17]. In this series GN as a cause of CKD reported in 18% of patients, while Samuel reported GN Aboriginal children and young adults have increased risk of ESRD mostly due to GN in people ≤ 40 years of age [18]. Samuel et al report agrees with the incidence reported with our results.…”
Section: Discussionsupporting
confidence: 88%
“…4,5,23,24 Similar to Dyck and colleagues, we report an age-and sex-adjusted rate of kidney failure that is 3-fold higher for First Nations than for non-First Nations people. 24 Previous studies, however, have not included an assessment of albuminuria or potential modifying effects of albuminuria on risk of progression of kidney disease in this population.…”
Section: Discussionsupporting
confidence: 85%
“…In fact, 9 of 10 children from this population with macroalbuminuria were shown to have either glomerulosclerosis or immunemediated disease on kidney biopsy (26). Recent national data support this finding, which showed that glomerulonephritis was the most common cause of end-stage renal disease in aboriginal children and adults ,40 years old, whereas diabetes started to predominate only after 40 years of age (27). Because the majority of youth with type 2 diabetes in Manitoba are of self-declared aboriginal heritage (5), the high background rate of immunemediated disease can be hypothesized to play an important role in the higher risk of chronic kidney disease in this population, likely potentiated by diabetes.…”
Section: Discussionmentioning
confidence: 82%